IMPLEMENTATION OF COLLABORATIVE LEARNING TO IMPROVE STUDENT COOPERATION IN LEARNING INDONESIAN LANGUAGE IN CLASS IV SDN 12 PALU - Moh. Yamin; Muhammad Jamhari; Isrofiah (LPPM Universitas Cipta Mandiri, 2025)
This research aims to determine the causes of students' lack of cooperation in learning Indonesian through the application of collaborative learning based on colored questions. This aims to find solutions to problems faced by researchers. From initial observations, it was found that the causes of lack of cooperation among students included; 1) Students choose friends to pair up in groups, 2) Students feel uncomfortable when in a group with friends who are not on the same bench and even show a resistant attitude when put together with students of medium ability. This research was carried out in 2 cycles, each cycle was carried out through 4 stages, namely planning, implementation, observation and reflection. Research data was obtained through direct observation which was documented on an observation sheet as the main data. Then supporting data is obtained through interview with indications of improvements from the previous cycle such as; 1) Students are actively involved in the group because each of them has a role. 2) Create positive interactions between students to respect each other's abilities. Apart from that, 3) Students share knowledge with each other in group work (peer tutoring). The application of collaborative learning based on colored questions is effective in improving students' cooperation abilities with the following details; In terms of indicators 1) Responsible for solving problems increased from 68% in cycle I to 81% in cycle II, 2) Willing to share, help and help friends from 68% in cycle I to 76% in cycle II, 3) Being in a work group when the activity progressed from 74% in cycle I to 84% in cycle II, and 4) Showing enthusiasm in doing the work from 63% in cycle I to 74% in cycle II.